The role of long-term combination training in reducing and maintaining of body fat in obese young adult women - Adi Pranoto; Roy Novri Ramadhan; Purwo Sri Rejeki; Muhammad Miftahussurur; Ghana Firsta Yosika; Triska Susila Nindya; Bhekti Lestari; Shariff Halim (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Reducing body weight and body fat is the primary goal for overcoming obesity. Lifestyle modifications with a non-pharmacological approach based on programmed physical exercise are recommended for increasing energy expenditure and reducing body weight and body fat. This study aims to analyze different types of exercise in reducing and maintaining body fat in obese young adult women. This study was a randomized controlled trial (RCT) with a true experimental design. A group of 28 sedentary overweight women were enlisted and provided with aerobic, strength, and mixed exercise regimens. Aerobic, resistance, and combined training programs were conducted with an intensity of 60-70% HRmax for aerobic, and 60-70% 1-RM for resistance. These sessions were performed 3x/week for 4 weeks. Measurement of body fat before-intervention and 24 hours after-intervention for 4 weeks using Seca mBCA 554. The one-way ANOVA test was utilized for statistical analysis, with a significance level of 5%. The findings demonstrated a significant reduction in body fat through all three forms of exercise, evident in the decrease in changes in body mass index, body weight, fat mass, and free fat mass (p ≤ 0.05). Additionally, all three exercise modalities led to a significant increase in changes in skeletal muscle mass in comparison to the control group (p ≤ 0.05). Our study results concluded that the combination type of exercise performed 3x/week for 4 weeks was more beneficial in lowering body fat and increasing muscle mass compared to aerobic exercise and resistance type exercise in obese young adult women.